2017
DOI: 10.1016/j.repbio.2017.01.001
|View full text |Cite
|
Sign up to set email alerts
|

The CatSper channel modulates boar sperm motility during capacitation

Abstract: The cation channel of sperm (CatSper) comprises four transmembrane subunits specifically expressed in human, equine, murine and ovine spermatozoa, apparently implicated in capacitation, hyperactivation and acrosome exocytosis. Western blotting and immunocytochemistry showed hereby that CatSper subunits are also present in boar spermatozoa, primarily over the sperm neck, tail and cytoplasmic droplets; albeit CatSper -1 presented in addition some distribution over the membrane of the acrosome and CatSper -2 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
49
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(64 citation statements)
references
References 58 publications
3
49
0
3
Order By: Relevance
“…In this regard, it is worth noting that calcium plays a crucial role during both sperm capacitation and acrosome reaction (Belmonte et al, 2016;Vicente-Carrillo et al, 2017), and that we previously identified two storage calcium sites (head and mid-piece) in boar spermatozoa . Interestingly, both observations are counteracted when GSH is present, which occurs together with changes in other sperm capacitation markers, such as motility, membrane lipid disorder and tyrosine phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, it is worth noting that calcium plays a crucial role during both sperm capacitation and acrosome reaction (Belmonte et al, 2016;Vicente-Carrillo et al, 2017), and that we previously identified two storage calcium sites (head and mid-piece) in boar spermatozoa . Interestingly, both observations are counteracted when GSH is present, which occurs together with changes in other sperm capacitation markers, such as motility, membrane lipid disorder and tyrosine phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of GSH on specific parameters, such as motility, membrane lipid disorder, mitochondrial membrane potential and intracellular calcium levels, also support the modulating role of GSH on sperm capacitation. In this regard, it is worth noting that calcium plays a crucial role during both sperm capacitation and acrosome reaction (Belmonte et al, 2016;Vicente-Carrillo et al, 2017), and that we previously identified two storage calcium sites (head and mid-piece) in boar spermatozoa . In this study, we observed that the effects of GSH on intracellular calcium levels were more apparent in Flu-o3-stained calcium (mainly located in the mid-piece) than in the 792 Andrology, 2018, 6, 781-797…”
Section: Discussionmentioning
confidence: 99%
“…Epididymal spermatozoa from male CatSper ‐KO mice are incapable of exhibiting hyperactivation by incubation in the capacitation‐supporting medium . Although the CatSper channels exist in bull and boar ejaculated spermatozoa, further experiments are necessary to demonstrate their functions in the occurrence of hyperactivation.…”
Section: Regulatory Mechanisms For Flagellar Hyperactivationmentioning
confidence: 99%
“…Epididymal spermatozoa from male CatSper-KO mice are incapable of exhibiting hyperactivation by incubation in the capacitation-supporting medium 64,66,67. Although the CatSper channels exist in bull and boar ejaculated spermatozoa,68,69 further experiments are necessary to demonstrate their functions in the occurrence of hyperactivation.In bulls, boars, and mice, hyperactivation can be induced immediately in uncapacitated spermatozoa by a short treatment with putative stimulator for IP 3 R "thimerosal." The thimerosal-induced hyperactivation is full-type (bulls and boars)/anti-hock (mice) 38,50,51,70.…”
mentioning
confidence: 99%
“…Interestingly, since in spermatozoa AR is a terminal event that occurs only once in cell life, different from what happens in secreting cells where the complex could be disassembled and recycled for further rounds of fusion, here the SNAREs are associated to form ternary cis-complex unstable and insensitive to neurotoxins. When AR takes place, calmodulin is activated by calcium intracellular concentration peak [39] and promotes the activation of RAB3A, which in turn allows the cis-SNAREs disassembly by SF/a-SNAP. Then, monomeric SNAREs form trans-complexes, causing the irreversible docking of the acrosome to the PM.…”
Section: Membrane Fusion and Acrosome Reactionmentioning
confidence: 99%